Evolução tectono-metamórfica do embasamento mesoarqueano do Domínio Carajás, Província Carajás - Silva, Marco Antonio Delinardo da, 1984- (2018)
Orientadores: Lena Virgínia Soares Monteiro, Ticiano José Saraiva dos Santos